Quelle réception sociale pour l’ingénierie écologique industrielle ? - Marion Amalric; Claudia Cirelli; Corinne Larrue (VertigO, 2015)
One of the main functions of natural wetlands is water treatment. Some industrial companies developed “Constructed wetlands” (CW) they added at the outlet of Waste Water Treatment Plant (WWTP) to improve water treatment and also to enhance ecological diversity. It is meant to create a standardised product, with a “green” content. Social sciences researchers involved in a research program on the topic were asked to evaluate the “social reception” (rather than acceptability) of the product. They used focus groups methodology to extract social representations of stakeholders concerning the constructed wetlands. The issue of the paper is to show that the acceptance of CW is more related to social, economical or landscape dimensions than to the technical reality of such a “product”. First, we show what are the factors of appreciation and of rejection. Then we show that biodiversity and green policies are not as well as valuated than the innovative dimension and territorial integration of CW.